Application of Optimal Control Strategies for the Spread of HIV in a Population - Marsudi Marsudi; Noor Hidayat; Ratno Bagus Edy Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
This paper presents an application of optimal control theory to assess the effectiveness of control measures on the spread of HIV in a population. This paper formulates and analyzes a deterministic mathematical model with use of condom, screening and therapy as control variables using optimal control theory and Pontryagin’s Maximum Principle. It formulates the appropriate optimal control problem and investigate the necessary conditions for the disease control in order to determine the role of unaware infectives in the spread of HIV using of condom, screening of unaware infective and antiretroviral therapy are used as the control items. The optimality system is derived and solved numerically.